Neuronize v2: Bridging the Gap Between Existing Proprietary Tools to Optimize Neuroscientific Workflows - Velasco, Ivan; Toharia, Pablo; Benavides-Piccione, Ruth; Fernaud-Espinosa, Isabel; Brito, Juan P.; Mata, Susana; DeFelipe, Javier; Pastor, Luis; Bayona, Sofia (Frontiers in Neuroanatomy, 2020)
Knowledge about neuron morphology is key to understanding brain structure and function. There are a variety of software tools that are used to segment and trace the neuron morphology. However, these tools usually utilize proprietary formats. This causes interoperability problems since the information extracted with one tool cannot be used in other tools. This paper aims to improve neuronal reconstruction workflows by facilitating the interoperability between two of the most commonly used software tools — Neurolucida (NL) and Imaris (Filament Tracer). The new functionality has been included in an existing tool —Neuronize— giving rise to its second version. Neuronize v2 makes it possible to automatically use the data extracted with Imaris Filament Tracer to generate a tracing with dendritic spine information that can be read directly by NL. It also includes some other new features, such as the ability to unify and/or correct inaccurately-formed meshes (i.e., dendritic spines) and to calculate new metrics. This tool greatly facilitates the process of neuronal reconstruction, bridging the gap between existing proprietary tools to optimize neuroscientific workflows.